2015
DOI: 10.1111/echo.12932
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Coronary In‐Stent Restenosis Using Dual‐Source Computed Tomography

Abstract: Stent inner diameter is a key factor influencing the imaging of the stent lumen. DSCT demonstrated a higher negative predictive value in ISR assessment, suggesting that it could replace CAG for assessing the patency of stents with a larger inner diameter (≥3 mm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…6 DS-CTA is a promising non-invasive method of assessing stent patency and can exclude significant ISR with high diagnostic values after vertebral artery ostium stenting. 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 DS-CTA is a promising non-invasive method of assessing stent patency and can exclude significant ISR with high diagnostic values after vertebral artery ostium stenting. 13…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Furthermore, previous researches have indicated that it is difficult to acquire the image of coronary stent-related blood vessel segments due to interference induced by calcified plaques and metal stent artifacts. 13 Additionally, stent artifacts with small inner diameters cannot easily be distinguished with accuracy. However, due to its rapid acquisition speed, high spatial and temporal resolution, and powerful image post-processing abilities, DS-CTA has been proven tremendously useful for examining the cardiovascular system with stent artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…After screening titles and/or abstracts, 3387 articles were excluded and remaining 135 articles were chosen for further inspecting. Through full-text review, 12 articles involving 13 studies, [8][9][10][11][12][13][14][15][16][17][18][19] with a total of 894 patients and 1384 assessable stents were finally included in the current meta-analysis.…”
Section: Data Analyses and Synthesesmentioning
confidence: 99%
“…This is partly due to the wide range of sensitivity (between 69% and 100%) and specificity (between 76% and 96%). [8][9][10][11][12][13][14][15][16][17][18][19] Thus, this study aimed at performing a meta-analysis, based on the currently available published articles, of the diagnostic accuracy of DSCTA in detecting CISR compared with ICA, to provide an objective evidence-based data for clinical and imaging diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The advent of new techniques is likely to reach smaller stents. 11 It remains a puzzle as to why CTA is singled out by the US. It does have the potential to reduce diagnostic invasive angiography volume 12 which would generate economic concerns for clinical practices and it does shunt that work for many centers, out of cardiology and into radiology departments.…”
Section: Slant Toward Invasive Coronary Angiographymentioning
confidence: 99%